Body structure for natural gas vehicles. - Sahari, Barkawi (2005)

(untitled)
A vehicle platform for agaseous fuel system that it can accommodate fuel piping and gas tanks transverse direction in in-line direction with all gas tanks mounted underneath the platform supported by means of snug fit components fitted to the mounting bar using means of detachable fasterners and gas tanks are arranged for ease of assembly, disassembly, maintenance, inspection service and replacement.